2019
DOI: 10.1200/jco.2019.37.15_suppl.5007
|View full text |Cite
|
Sign up to set email alerts
|

Decreased fracture rate by mandating bone-protecting agents in the EORTC 1333/PEACE III trial comparing enzalutamide and Ra223 versus enzalutamide alone: An interim safety analysis.

Abstract: 5007 Background: Skeletal fractures, pathological or not, are a frequent and underestimated side-effect of systemic treatment of metastatic castration resistant prostate cancer (mCRPC). The ERA223 trial (NCT02043678) was recently unblinded following the report of a significant increase in the fracture rates when abiraterone is combined with Ra223. Hence, FDA and EMA advised against this combination. The question whether mandated use of bone protecting agents (BPA), zoledronic acid or denosumab, would have mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
40
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 0 publications
2
40
0
3
Order By: Relevance
“…19 As a result, the cumulative risk of fracture at 12 months dropped to 0% in both treatment groups. 19 While the results of the PEACE III study have not been fully validated, it is striking that only one fracture has been observed since mandating OPA administration. 19 The decrease in fracture risk was not as dramatic in the ERA 223 trial, and many of the patients who sustained a fracture while receiving Ra-223 and AAP (21%) or AAP alone (24%) were also taking an OPA.…”
mentioning
confidence: 94%
See 4 more Smart Citations
“…19 As a result, the cumulative risk of fracture at 12 months dropped to 0% in both treatment groups. 19 While the results of the PEACE III study have not been fully validated, it is striking that only one fracture has been observed since mandating OPA administration. 19 The decrease in fracture risk was not as dramatic in the ERA 223 trial, and many of the patients who sustained a fracture while receiving Ra-223 and AAP (21%) or AAP alone (24%) were also taking an OPA.…”
mentioning
confidence: 94%
“…denosumab, zoledronic acid) in combination with Ra-223. 19 The use of OPAs in prostate cancer is not a new idea. In fact, a phase III study has examined the relative efficacies of denosumab, a RANKL inhibitor, and zoledronic acid, a bisphosphonate, in patients with prostate cancer, finding that denosumab was superior for the prevention of SREs.…”
mentioning
confidence: 99%
See 3 more Smart Citations